Handling Domain Knowledge in Design and Analysis of Engineering Models - Hacid, Kahina; Ait-Ameur, Yamine (Electronic Communications of the EASST, 2018)
The development of complex systems, involves several domain experts and several models corresponding to different analyses (views) of the same system. No explicit information recording the characteristics of the performed system analyses is given. We propose a stepwise approach to keep trace of the process that allows a system designer to build a model analysis first, by making explicit definition of a descriptive model to describe the features of an analysis and second, by making explicit definition of the required concepts and properties borrowed from a design model to trigger a given model analysis.The approach is deployed using Model Driven Engineering (MDE) techniques and illustrated on an academic case study.